THE INFLUENCE OF ORGANIZATIONAL CLIMATE, WORK COMMITMENT, JOB SATISFACTION ON EMPLOYEE ACHIEVEMENT IN REGIONAL SECRETARIAT OFFICE BENGKULU PROVINCE - M Rafi Ariansyah; Dasman Lanin; Erianjoni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research departs from the problememployee performance is still low because it is not supported by adequate work facilities and infrastructure so that employees are unable to channel their abilities. The role of superiors in influencing employees in order to achieve organizational goals has not been fulfilled, due to a lack of communication between superiors and their subordinates. The average number of employees at the Regional Secretariat of Bengkulu Province is only 14.7% of employees who are committed to work and 85.3% of employees are not committed to work, andthe low level of employee job satisfaction is due to the lack of awards and rewards given by the organization. This study aims to determine the effect of organizational climate, work commitment, job satisfaction and work performance by the Bengkulu Provincial Secretariat. This type of research is associative quantitative research. The sampling technique used in this research is census or total sampling. The population in this study were all employees at the Bengkulu Provincial Secretariat, totaling 48 employees. The sample technique used is the slovin formula with a sample of 48 employees. The results showed that (1) organizational climate had a positive or significant effect on work performance variables with an Adjusted R Square table value of 0.397, which was 39.7 and a significance value of 0.000. (2) Work commitment has a positive or significant effect on work performance variables with an Adjusted R Square value of work commitment variable of 0.724 and a significance of 0.000. (3) Job satisfaction has a positive or significant effect on work performance variables with an Adjusted R Square value for job satisfaction variables of 0.500 and a significance of 0.000. (4) Organizational climate, work commitment and job satisfaction have a positive or significant effect on work performance variables with an Adjusted R Square value of 0.727 and a significance value of 0.000. 500 as well as for a significance of 0.000. (4) Organizational climate, work commitment and job satisfaction have a positive or significant effect on work performance variables with an Adjusted R Square value of 0.727 and a significance value of 0.000. 500 as well as for a significance of 0.000. (4) Organizational climate, work commitment and job satisfaction have a positive or significant effect on work performance variables with an Adjusted R Square value of 0.727 and a significance value of 0.000.